Max Weber & Islam - Huff, Toby E.; Schluchter, Wolfgang (Routledge, 2018)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- Preface -- Introduction -- 1. Hindrances to Modernity : Max Weber on Islam -- 2. The Institutionalization of Early Islamic Societies -- 3. Aspects of Islamization: Weber's Observations on Islam Reconsidered -- 4. Islamization in Late Medieval Bengal: The Relevance of Max Weber -- 5. Max Weber and the Patrimonial Empire in Islam: The Mughal Case -- 6. Paradise or Hell? The Religious Doctrine of Election in Eighteenth and Nineteenth Century Islamic Fundamentalism and Protestant Calvinism -- 7. Weber and Islamic Reform -- 8. Secularization, Weber, and Islam -- 9. Weber, Islamic Law, and the Rise of Capitalism -- 10. Weber and Islamic Sects -- 11. Weber's Analysis of Islam and the Specific Pattern of Islamic Civilization -- Bibliography -- Contributors -- Index
Keywords: Konferenzschrift; Aufsatzsammlung; Islam; Weber, Max